Research on the relationship between bamboo-based product design attributes and consumer satisfaction - Xue, Yun; Abd Rahman, Khairul Aidil Azlin; Mohd Ariffin, Noor Fazamimah; Mohd Ali, Noor Azizi (Forest Products Society, 2024)
Sustainable low-carbon design is actively guiding the public’s green consumption and use of forest resources. With the slogan of replacing plastic with bamboo and the optimization of bamboo’s organizational structure and processing form, bamboo is becoming more and more designable. However, we found that there are still many views expressing dissatisfaction with bamboo products, among which homogeneity and insufficient design differentiation are the most frequent. On the basis of this, we obtained attributes for measuring bamboo product satisfaction through literature review, conducted a questionnaire survey of 463 customers to obtain data, and empirically analyzed attributes such as product creativity (PC), product quality (PQ), product fashion (PF), soft added value (SV), and shopping convenience (SC). We assessed the impact on consumer satisfaction (CS), as well as the impact on satisfaction under the moderating effect of brand image (BI). The results show that PF, BI, PC, and PQ positively affect CS; PF, PQ, and SV positively affect the BI; PF, SV, and PQ positively affect CS through the intermediary effect of BI. SV has an insignificant effect on CS, but can positively affect CS through BI, indicating that there is a partial mediating effect of BI. However, the mediating effect of BI on PC, SC, and CS has not been verified. Finally, on the basis of the conclusions, several countermeasures and suggestions for bamboo product innovation are put forward. © 2024 Forest Products Society. All rights reserved.